Modeling Chaos and Image Processing in Distributed Architectures - Mucheroni, Marcos Luiz; Saito, José Hiroki; Machado, Giandri; Rosa, Reinaldo R.; Sawant, Hanumant S.; Moron, Célio Estevan (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 2000: Anais do XII Symposium on Computer Architecture and High Performance ComputingDO - 10.5753/sbac-pad.2000.41218, 2000)
The emergency of solving non-linear systems using chaos theory and the solution of innumerable problems using image processing approaches, leads to the use of specific machines, which explores the data and instruction parallelism. The dynamic system monitoring chaotic nonlinear systems, starting form equations or time series is quite common,but the use of combinig techniques of image processing with chaos approaches isn’t usual. In this paper, the combing techniques are used to characterize signals obtined from solar explosion, from which it is calculated the embedding dimension, and the power spectra. The proposed techniques is being implemented in a parallel processing machine, PAD, and the performance is discussed.